2021
DOI: 10.26442/00403660.2021.01.200588
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length as a biomarker of the risk of cardiovascular complications in patients with coronary heart disease

Abstract: Aim. To study the effect of oxidative stress and telomere length in the chromosomes of blood leukocytes in patients with coronary heart disease (CHD) on the development of cardiovascular complications. Materials and methods. In 119 patients with CHD, the level of oxidatively modified low-density lipoproteins (ox-LDL) in blood plasma and the length of telomeres in nuclear blood cells were determined during the examination. After 5 years, a telephone survey of patients (or their relatives) was conducted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Ashley et al found that there existed a certain relationship between HDL-C and telomere length [ 13 , 14 ]. A strong negative relationship between LDL and telomere length was reported in patients with cardiovascular complications in a case-investigation study [ 15 ]. Moreover, Alison et al discovered that shortening of telomere length in South Asian population with type 2 diabetes was inversely associated with TG and TC [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ashley et al found that there existed a certain relationship between HDL-C and telomere length [ 13 , 14 ]. A strong negative relationship between LDL and telomere length was reported in patients with cardiovascular complications in a case-investigation study [ 15 ]. Moreover, Alison et al discovered that shortening of telomere length in South Asian population with type 2 diabetes was inversely associated with TG and TC [ 16 ].…”
Section: Introductionmentioning
confidence: 99%